Therapeutic Effects of Garlic (Allium Sativum) Compounds from Different Pretreatment Processes on Women's Reproductive Health: A Narrative Review - Permata, Dear Ayu; Nurseta, Tatit; Ariani, Novida (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
Women’s reproductive health disorders occur due to oxidative stress and can be treated with antioxidant intake. One of them is by utilizing the phytochemical content of garlic (Allium sativum). The semi-systematic review method helps authors to identify the pretreatment of garlic compound S-allyl cysteine (SAC) on women's reproductive health. The literature collection was adjusted to the study of the treatment of garlic compounds with search keywords used “Garlic”, “Reproductive health”, “S-allyl cysteine”, and “Women”. The sources used come from online publications from 2010 to 2024. The form of research in the literature review was carried out on test animals, test cells, and test treatments on humans. The selection of information in the reviewed article refers to the year of publication, test products, sample objects, research methods, results, and discussion. The interpretation of the results will be explained descriptively based on the review analysis. Ten study articles have a positive effect of garlic compounds on women's reproductive health. The pretreatment carried out was garlic extract, garlic powder, hexane extract of aged black garlic, dried garlic powder, and aged garlic (black) extract. This review shows that garlic has a main compound S-allyl cysteine (SAC). The bioactive components of garlic can stimulate antioxidant activity and increase the fertility of reproductive organs because it increases the metabolism of oocytes, hormonal regulation, and the maturation of the endometrium. The results of garlic pretreatment showed that aged garlic (black garlic) extract contained S-allyl cysteine (SAC) with more compounds, was more stable, soluble in water, and had minimal toxic content. It allows black garlic (SAC) to have prophylactic properties at the clinical level, so it is possible to develop research on black garlic's effects on women's reproductive health.